Peran Pendidikan Hukum Dalam Meningkatkan Kesadaran Hukum Masyarakat: Pendahuluan; Metode; Hasil dan Pembahasan; Kesimpulan - Adi Nur Aziz; Milatul ija; Nailul Mafazah; Ayu Maya Damayanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Legal education plays a crucial role in shaping and enhancing public legal awareness. Poor public understanding of the law often leads to a lack of compliance with prevailing regulations in social life. This study aims to examine the role of legal education in enhancing public legal awareness through a literature review approach. The research method used was qualitative research, with data collection techniques including searching scientific journals, books, and relevant laws and regulations obtained online. The study results indicate that legal education contributes significantly to improving public understanding of legal rights and obligations and encouraging compliance with regulations. Sustainable legal education can build a strong legal culture within society. Thus, legal education is a strategic instrument in creating order, justice, and a better social life.